2014
DOI: 10.1038/tpj.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic inheritance of paclitaxel-induced sensory peripheral neuropathy driven by axon outgrowth gene sets in CALGB 40101 (Alliance)

Abstract: Peripheral neuropathy is a common dose-limiting toxicity for patients treated with paclitaxel. For most individuals there are no known risk factors that predispose patients to the adverse event, and pathogenesis for paclitaxel-induced peripheral neuropathy is unknown. Determining whether there is a heritable component to paclitaxel induced peripheral neuropathy would be valuable in guiding clinical decisions and may provide insight into treatment of and mechanisms for the toxicity. Using genotype and patient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…MLM and polygenic modeling methods are now being applied to PGx data. MLM/GCTA analyses have been used to investigate asthma PGx traits [87], and paclitaxel-induced sensory peripheral neuropathy [88]. …”
Section: What Have We Learned?mentioning
confidence: 99%
See 1 more Smart Citation
“…MLM and polygenic modeling methods are now being applied to PGx data. MLM/GCTA analyses have been used to investigate asthma PGx traits [87], and paclitaxel-induced sensory peripheral neuropathy [88]. …”
Section: What Have We Learned?mentioning
confidence: 99%
“…Chhibber et al (2014) [88] investigated a polygenic etiology of paclitaxel-induced neuropathy. They estimated the variance explained by common SNPs (MAF >1%) for two outcomes: the maximum grade of sensory peripheral neuropathy, and the dose at first instance of peripheral neuropathy.…”
Section: What Have We Learned?mentioning
confidence: 99%
“…In a Cancer and Leukemia Group B clinical trial, the loci identifi ed that were associated with paclitaxel-induced neuropathy were in genes involved in axon outgrowth (Baldwin et al 2012 ;Chhibber et al 2014 ). Although, in retrospect, these fi ndings make sense, they provide a new perspective or paradigm for pharmacogenetics.…”
Section: Does Genetic Make-up Infl Uence Recurrence and Survival?mentioning
confidence: 88%
“…FDG4 is associated with the hereditary neuropathy condition of CharcotMarie-Tooth disease. Subsequent pathway and modeling work with this data set have suggested that a hereditable predisposition to this toxicity may lie in genes involved in axon outgrowth (Chhibber et al 2014 ). Another trial specifi cally focused on more rare variants using massively parallel sequencing of 20,794 genes associated with heredity neuropathy from patients who had received paclitaxel-based chemotherapy (Beutler et al 2013 ).…”
Section: Identifying Host Factors Related To Risk For Cipnmentioning
confidence: 98%